AKTIVITAS ANTIBAKTERI EKSTRAK JINTAN HITAM (NIGELLA SATIVA) TERHADAP BAKTERI STAPYLOCOCCUS AUREUS (ATCC) - Rawati Siregar; Sri Junita Nainggolan; Aminah Br Saragih (Poltekkes Kemenkes Medan, 2026)
Dental and oral health problems, including caries and plaque, are caused by bacterial infections such as Staphylococcus aureus. This bacterium plays a role in the formation of plaque biofilm, which can lead to caries if not controlled. One approach to control that is being developed is the use of natural ingredients with antibacterial activity. Black cumin (Nigella sativa) contains active compounds like flavonoids, saponins, tannins, and alkaloids, which have potential as antibacterials. This study aimed to determine the antibacterial activity of black cumin ethanol extract against the growth of Staphylococcus aureus (ATCC) bacteria. The research used an experimental method with a post- test only control group design. The extract was obtained through maceration with 96% ethanol and tested at three concentrations: 25%, 50%, and 75%. Chlorhexidine was used as a positive control, and Dimethyl Sulfoxide (DMSO) as a negative control. The study results indicated that black cumin ethanol extract (EEJH) showed comparable potential to chlorhexidine starting from a 50% concentration. However, increasing the concentration to 75% did not show a greater increase in antibacterial potential compared to the positive control group (chlorhexidine). In conclusion, black cumin (Nigella sativa) ethanol extract was able to significantly inhibit Staphylococcus aureus bacteria at a 25% concentration.